Kegiatan Donor Darah Akademi Keperawatan St. Elisabeth Lela Bersama Palang Merah Indonesia Kabupaten Sikka - Mane, Gabriel; Kuwa, Maria Kornelia Ringgi; Gaharpung, Mediatrix Santi; Wega, Marianus Oktavianus; Reong, Antonia Rensiana; Sulastien, Herni (PT.Mantaya Idea Batara, 2023)
Blood donation is an activity of donating blood, both for replacement blood needs and as a direct donor, which has an important function in various health services. The death rate due to the unavailability of blood reserves in developing countries is relatively high. This community service activity aims to assist the Indonesian Red Cross (PMI) in collecting and socializing blood donors to the public. The death rate due to the unavailability of blood reserves in developing countries is relatively high. In fact, the percentage of blood donors is still low which causes limitations in meeting the increasing need for blood. This limited number of blood donors can be caused by a lack of knowledge about blood donors, wrong assumptions or perceptions about blood donation, or fear of technical procedures for blood donation.